Social Environment and Internet Engagement as Predictors of Cyberbullying in Young People - Herawati; Shalsa Nabila; Putri Nirmala; Ummul Khaeri Masna (Sakura Digital Nusantara, 2025)
Social media has become an important part of young people's lives, not only as a means of communication and entertainment, but also as a space for intense social interaction. The high intensity of internet use brings both positive opportunities and risks, one of which is cyberbullying which has a serious impact on mental health, such as anxiety and depression. This study aims to analyze the effect of internet usage intensity and social environment on cyberbullying tendencies in college students. The research method used a quantitative approach with a cross-sectional design. Data were obtained through a five-point Likert scale online questionnaire filled out by 83 respondents from various generations. Descriptive analysis showed that aspects of social media use were quite high, while direct experience of cyberbullying was relatively lower. Social environment support was moderate, but awareness of cyberbullying prevention was high. The findings indicate that the intensity of internet use potentially increases the risk of cyberbullying, but social environmental factors and digital awareness can serve as important protections. This research provides practical contributions in the form of recommendations for digital literacy, strengthening family support, and social media monitoring to create a safer digital ecosystem for the younger generation.